Strategi Bertutur Fisioterapis - Arni Chairul (Ranah: Jurnal Kajian Bahasa, 2021)
This study aims to find out how to use the physiotherapist's speech strategy at RSU Haji Medan according to the theories of Brown and Levinson. This research uses a qualitative approach with the case study method while data obtained through observation and interviews. This research found that there are 2 speech strategies used by physiotherapists at RSU Haji Medan. First, on record with positive politeness strategy contained in request directive speech acts (100%), question directive speech acts (100%), requirements directive speech acts (100%), agreement directive speech acts (100%), advisories directive speech acts (71%). Second, bald-on record strategy contained in prohibition directive speech acts (100%) and advisories directive speech acts (29%).